Multiplicidad funcional de la representación molecular : implicaciones en la enseñanza y aprendizaje de la química (2006)
ABSTRACT: This tex has the sense of a thoughtful about some epistemology aspect the representation functional multiplicity of molecular, with the propouse to give an opportunity of educational investigation in chemistry in the ferst levels of professionals studies. Because of the molecular structure concept is assumed in chemistry teaching in simple way, as the corresponding different representations are reduced to gross static models, adopted in a thoughtless way as ingenuous pictographic signs, in order to be repeat from the text or from the professor’s writing to the students’ writing without comprehension of the symbols. The teaching and learning of chemistry is too far a way from conceptual progress; plurality and functionality of the meanings of substances representations and its physic-chemical modifications assumed as dynamics objects and trajectories. This concept that in the chemical knowledge includes empirical, theoretical, physical, mathematical and epistemological aspects, is complex and it is necessary to approach it in its complexity. An epistemology perspective of how chemists have created a great amount of representations, meanings and theories for this concept when they solve situations and exercise comprehension, explanation and prediction, acquire a great value for teaching and learning chemistry in a classroom. The practice of epistemological perspective will be to promote approximations to plurifunctional thinking about the molecular structure, well supported in educational research in the field of mental representations, in particular the related studies with mental models and conceptual fields that stimulate the research for psychological process to learn concepts and models in physics and mathematics when students resolve classes of situations.